ANALISA AKUNTABILITAS BELANJA HIBAH PADA PEMERINTAHAN KOTA YOGYAKARTA - WARDOYO, DWI URIP; Rachma, Annisa Aulia; DWI N, ANNISAA INDAH; HANIF, AZZARIF (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2022)
This study aims to analyze the accountability of subsidy spending to the Yogyakarta city government. This research is a qualitative research with an exploratory approach. The data were obtained through in-depth interviews from the literature study. It was concluded that there were bottlenecks for all six grant expenditure management processes. These obstacles arise in the accountability and reporting processes. These problems are (1) compliance problems that occur in the process of implementing accountability for grant spending, (2) regulatory constraints where regulations have not been conveyed to grant managers, especially those related to regional apparatus, (3) constraints in budget implementation. grant spending which takes a longer process because it has to go through several stages, (4) constraints in terms of lack of human resource competence and accountability and reporting capabilities, and (5) limited supporting facilities in realizing accountability for grant spending.This study reveals that coordination between grant-making institutions, information and communication between grant managers and grantees is critical in achieving accountability. Dissemination of regulations regarding grant issuance, sanctions, and assistance to the community or grant funders will contribute to better accountability for grant spending. Various efforts have been made to minimize delays in submitting accountability reports for grant funds, including imposition of penalties, ensuring accountability between grant managers, request in-depth reporting to grantees and the preparation of standardized accountability reports to facilitate the preparation of accountability reports by grantees. easier and helps reviewers verify reports.